Le gameplay comme prolongement de la construction narrative - Alain Zind (Conserveries Mémorielles)
This article questions the narrative dimension and Paul Ricoeur’s « mise en intrigue » that can be relative to videogames, toward its interactive solutions – the gameplay. In other words, the purpose is to observe how, in certain cases, game experience can fully contribute to build the videogame narration, while questionning different terms, such as actors, authors, individual and collective memory.